Development of Derivative and Integral Module as Calculus Lecture Support - Tika Karlina Rachmawati; T. Tutut Widiastuti A (Department of Mathematics Education, UIN Sunan Gunung Djati Bandung, West Java, Indonesia, 2022)
Penelitian ini bertujuan untuk mengetahui pengembangan modul materi Turunan dan Integral ditinjau dari tingkat validitas, kepraktisan, efektivitas modul sebagai penunjang perkuliahan mahasiswa prodi Pendidikan Matematika yang dinilai oleh ahli materi dan ahli media serta perbedaan peningkatan kemampuan pemecahan masalah matematis antara kelas yang menggunakan modul Turunan dan Integral dengan kelas yang tidak menggunakan modul Turunan dan Integral. Pengembangan modul Turunan dan Integral yang diperuntukkan untuk mahasiswa prodi Pendidikan Matematika dilakukan melalui beberapa tahap dalam model Research and Development (RnD) yang meliputi research and information collecting, planning, develop preliminary form of product, preliminary field testing, main product revision, main field testing, operational product revision, operational field testing, final product revision, dissemination and implementation. Hasil pengembangan modul Turunan dan Integral menunjukkan valid, praktis dan efektif sehingga layak digunakan pada pembelajaran Kalkulus. The purpose of this study was determine the development of the Derivative and Integral material module in terms of the level of validity, practicality, and effectiveness of the module as a lecture support for students of the Mathematics Education study program assessed by material experts and media experts as well as differences in increasing mathematical problem solving abilities between classes using module Derivatives and Integrals with classes that do not use the Derivatives and Integral modules. The development of the Derivative and Integral module which is intended for students of the Mathematics Education study program is carried out through several stages in the Research and Development (RnD) model which includes research and information collecting, planning, develop preliminary form of product, preliminary field testing, main product revision, main field testing, operational product revision, operational field testing, final product revision, dissemination and implementation. The results of the development of the Derivative and Integral module show that this module is valid, practical and effective so that it is suitable for use in Calculus learning.